Pengaruh Komunikasi Dan Promosi Jabatan Terhadap Prestasi Kerja Karyawan Di PT. Indomarco Prismatama Cabang Palembang - Lilian Lilian; Muhni Pamuji (LPPM Universitas Multi Data Palembang, 2021)
The results of this study indicate the results of multiple linear analysis as follows: y = 16.220 + 0.602 X1 +0.19 X2 + e. The value of 16.220 is work performance, the value of 0.602 is the communication variable (X1) and the value of 0.19 is the value of the job promotion variable (X2), and based on the partial test results using the t test, the results show the value of Communication (X1) 3.547. with a significant level value of 0.001 < 0.05. This means that Ho is rejected and Ha is accepted. This shows that there is a significant influence between Communication on Employee Performance at PT. Indomarco Prismatama Cab Palembang. Furthermore, the value of promotion (X2) - 0.281 with a significant value of 0.03 < 0.05. This means that Ho is rejected and Ha is accepted. This shows that there is a significant influence between Job Promotion on Employee Performance at PT. Indomarco Prismatama Cab Palembang. And from the results of research conducted to analyze the coefficient of determination, it is known that the R square value is 0.275. This means that 27.5% of the job performance variable can be explained by the communication and job promotion variables. Meanwhile, the remaining 72.5% job performance is influenced by other variables not examined in this study.